2014
DOI: 10.3892/ol.2014.1893
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fluid hyperthermia inhibits the growth of breast carcinoma and downregulates vascular endothelial growth factor expression

Abstract: The application of magnetic fluid hyperthermia (MFH) with nanoparticles has been shown to inhibit tumor growth in several animal models. However, the feasibility of using MFH in vivo to treat breast cancer is uncertain, and the mechanism is unclear. In the present study, it was observed that the intratumoral administration of MFH induced hyperthermia significantly in rats with Walker-265 breast carcinomas. The hyperthermia treatment with magnetic nanoparticles inhibited tumor growth in vivo and promoted the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Previous studies of magnetic fluid hyperthermia showed that the therapeutic effects could be strengthened by combination with radiotherapy and chemotherapy [30]. Magnetic fluid hyperthermia has been used to treat various cancers, such as breast cancer and liver cancer, and the effects have been well documented [31, 32]. However, the effect of magnetic fluid hyperthermia on LCSCs is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of magnetic fluid hyperthermia showed that the therapeutic effects could be strengthened by combination with radiotherapy and chemotherapy [30]. Magnetic fluid hyperthermia has been used to treat various cancers, such as breast cancer and liver cancer, and the effects have been well documented [31, 32]. However, the effect of magnetic fluid hyperthermia on LCSCs is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4A presents the experimental schedule. Research demonstrated that reduction in tumor growth can be enhanced by the number of MFH treatments (34,35). For this purpose, three MFH treatments were scheduled 48 hours apart.…”
Section: Hspa6 Silencing and Mfh Reduced Tumor Growth In Vivomentioning
confidence: 99%
“…In a study on treating breast and pancreatic cancer using MFH, positive treatment outcome was obtained where a decline in the cancer cell proliferation and an increase in the apoptosis and necrosis were observed [78]. Another study on the rat breast carcinoma model showed that hyperthermia could inhibit tumor growth by downregulating the vascular endothelial growth factor and inhibiting the angiogenesis process in the tumor [79]. …”
Section: Magnetic Fluid Hyperthermiamentioning
confidence: 99%